Different Types of Sukuk in Companies Listed in Bei - R. , Susanto; R. , Achmad Drajat Aji Sujai; Dewi Oktari, Sari; Ramdan Padmakusumah, Rizal (International Journal of Psychosocial Rehabilitation, 2020)
One form of Islamic financial instrument that has been widely published either by the corporation or by the state is sukuk. For issuers, issuing Islamic bonds (sukuk) means also utilizing certain opportunities. The issuer may acquire a broader funding source, both conventional and Islamic investors. Moreover, the innovative structure of Islamic bonds also offers an opportunity to gain a competitive capital cost and benefit. This study aims to determine the effect of different types of Islamic bonds (sukuk) in companies listed on the Stock Exchange. The method used by the researchers is to test the diversity using chi-square statistics with data collection based on the financial statements of some companies listed on the Stock Exchange. The results showed.